2009
DOI: 10.1007/s11104-009-9898-z
|View full text |Cite
|
Sign up to set email alerts
|

Winter wheat roots grow twice as deep as spring wheat roots, is this important for N uptake and N leaching losses?

Abstract: Cropping systems comprising winter catch crops followed by spring wheat could reduce N leaching risks compared to traditional winter wheat systems in humid climates. We studied the soil mineral N (N inorg ) and root growth of winterand spring wheat to 2.5 m depth during 3 years. The roots of the winter and spring wheat penetrated the soil at a similar rate (1.3 mm o C day −1 ) and by virtue of its longer growing period, winter wheat reached depths of 2.2 m, twice that of spring wheat (1.1 m). The deeper rootin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(136 citation statements)
references
References 36 publications
(42 reference statements)
11
114
3
1
Order By: Relevance
“…In the winter rye crop N inorg was already low in May, even after onion leaving high N inorg levels in the autumn, but this N inorg had probably already been taken up by the winter rye in the early spring. In a previous study winter wheat was found to take up much soil N already before mid April under similar conditions (Thorup- Kristensen et al, 2009), again confirming the typically higher N efficiency of cereal crops. Finally, cereal crops offer better options for introducing fertility building crops into the system than most vegetables do, as cereals allow undersowing of fertility building crops and because small yield losses caused by their establishment can more easily be tolerated in cereal crops than in vegetables.…”
Section: Reduced Nutrient Losses To the Environmentsupporting
confidence: 64%
“…In the winter rye crop N inorg was already low in May, even after onion leaving high N inorg levels in the autumn, but this N inorg had probably already been taken up by the winter rye in the early spring. In a previous study winter wheat was found to take up much soil N already before mid April under similar conditions (Thorup- Kristensen et al, 2009), again confirming the typically higher N efficiency of cereal crops. Finally, cereal crops offer better options for introducing fertility building crops into the system than most vegetables do, as cereals allow undersowing of fertility building crops and because small yield losses caused by their establishment can more easily be tolerated in cereal crops than in vegetables.…”
Section: Reduced Nutrient Losses To the Environmentsupporting
confidence: 64%
“…In this condition, there were very small amounts of N presented in deep layers of the soil. Thus, the deep rooting of winter wheat is not an effective way to access N as has been suggested by Thorup-Kristensen et al (2009). In our study, however, we were not able to determine the reason why winter-type varieties exhibited deeper root system architecture than spring-type varieties.…”
Section: Discussionmentioning
confidence: 56%
“…Oyanagi (1994) have found that wheat varieties bred for western Japan tend to have shallower root systems than varieties bred for eastern Japan, and explained this regional difference as an adaptation to the more abundant soil moisture in western Japan. Thorup-Kristensen et al (2009) have suggested that the deeper rooting of winter-type wheat enables more effective usage of N in the lower levels of the soil due to N leaching. Manschadi et al (2008) have found that drought-tolerant varieties tend to have deeper root systems compared to susceptible varieties.…”
Section: Discussionmentioning
confidence: 99%
“…The root density distributions showing maximal densities at greater depths are markedly different from the root density profiles that have been observed for winter wheat using soil coring in loamy soil (Zhang et al, 2004) and in soils with seven different textures (from clay to sandy loam) (e.g., White et al, 2015;Zhang et al, 2004). This might on the one hand be due to a great amount of water stored at those depths in the silty soil but probably also due to nutrient distribution in the soil profile at this site, which might have promoted root development in deeper soil layers (Thorup-Kristensen et al, 2009;Yang et al, 2003). On the other hand, some studies indicated that root length densities estimated from rhizotubes may underestimate the root densities in surface soil layers due to temperature effects (Fitter et al, 1998) or roots growing parallel to the horizontal plane not intersecting the tube surface (Meyer and Barrs, 1991).…”
Section: Effect Of Water Treatment On Crop and Root Developmentmentioning
confidence: 98%